The Relationship between Predisposing Factors and Community Participation in the Utilization of Communal Wastewater Treatment Plants (IPAL) in the Siboas Environment, Sihasto Village, Parlilitan District 2021 - Rosalinda Noviyanti Hasugian (Paspama Institute, 2023)
Sanitation is a deliberate behavior in cultivating clean living with the aim of preventing humans from coming into direct contact with dirt and other dangerous waste materials. Based on interviews with 8 families in the Siboas neighborhood of Sihasto Village, they did not use the IPAL because they felt that using the IPAL was of no benefit, did not want to dismantle the old sewer pipe to the IPAL because of costs and did not want to disturb their activities. The aim of this research is to determine the relationship between predisposing factors and community participation in the communal Waste Water Treatment Plant (IPAL) program in the Siboas neighborhood, Sihasto Village, Parlilitan District. This research design uses an analytical survey with a cross sectional approach. Data analysis used univariate analysis and bivariate analysis with the chi-square statistical test. The results of the chi-square test analysis show the value of each variable, including knowledge obtained p-value = 0.020, attitude p-value = 0.002 and economic status obtained p-value = 0.011. The conclusion of this research is that there is a relationship between knowledge, attitudes and economic status with community participation in the Communal IPAL program in the Siboas Environment, Sihasto Village, Parlilitan District. It is recommended to the Head of the Community Self-Help Group (KSM) that this research can be used as input to the community regarding the communal Waste Water Treatment Plant program in the Siboas Environment, Sihasto Village, Parlilitan District 2021, such as: Increasing appropriate and clear education to the community about the benefits and advantages of the IPAL program in preventing disease and maintaining environmental health in the community.